Grain‐scale supercharging and breakdown on airless regoliths. Issue 10 (25th October 2016) - Zimmerman, M. I.; Farrell, W. M.; Hartzell, C. M.; Wang, X.; Horanyi, M.; Hurley, D. M.; Hibbitts, K.
Abstract: Interactions of the solar wind and emitted photoelectrons with airless bodies have been studied extensively. However, the details of how charged particles interact with the regolith at the scale of a single grain have remained largely uncharacterized. Recent efforts have focused upon determining total surface charge under photoemission and solar wind bombardment and the associated electric field and potential. In this work, theory and simulations are used to show that grain‐grain charge differences can exceed classical sheath predictions by several orders of magnitude, sometimes reaching dielectric breakdown levels. Temperature‐dependent electrical conductivity works against supercharging by allowing current to leak through individual grains; the balance between internal conduction and surface charging controls the maximum possible grain‐to‐grain electric field. Understanding the finer details of regolith grain charging, conductive equilibrium, and dielectric breakdown will improve future numerical studies of space weathering and dust levitation on airless bodies. Key Points: Grain‐to‐grain electric fields can grow orders of magnitude stronger than classical sheath predictions Supercharged grains could experience frequent dielectric breakdown on asteroids and the Moon Differential breakdown rates in lunar crustal magnetic fields could play a role in lunar swirl formation